Hospital costs of immunopreventable diseases in the economically active population in Brazil - Élide Sbardellotto M. da Costa (BMC, 2021)
Abstract Background Immunopreventable diseases are a public health reality in Brazil and worldwide, a reality that is not exclusive to children, but affects the adult population. Objectives Discriminating the total costs of hospitalizations from immunopreventable diseases in the population aged 20 to 59 years. Methods A population, observational, descriptive, retrospective study was conducted with secondary information from DATASUS to discriminate the hospitalizations associated with immunopreventable diseases in Brazil and their care costs, within the Scope of the SUS, between 2008 and 2018, in the economically active population (20 to 59 years). Results It was analyzed 127,746 hospitalizations for immunopreventable diseases, (27.92% of all hospitalizations) were observed in the adult population, totaled R$115,682,097.54 (29.72% of the total costs). Of this population studied, 51.48% were registered as male; 66.74% were associated with influenza disease; 16.05% to chickenpox/herpes zoster infection and 7.55% to acute hepatitis B infections. The trend analysis of the time series of hospitalizations in this population showed a stationary trend. Conclusions The 127,746 hospitalizations could be avoided with immunization, and 127,746 workers who could be working and not hospitalized. There were also R$115,682,097.54 that could be invested in other public health needs, which became necessary for the treatment of preventable diseases.